Wear characterisation in milling of Ti6Al4V : a wear map approach - Oosthuizen, Gert Adriaan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Industrial Engineering))--University of Stellenbosch, 2010.